Особистісна готовність до професійної діяльності психолога - Токар, Юлія Андріївна; Tokar, Yuliya Andriyivna (Ірпінь, 2024)
Досліджено особливості основних підходів до феномену тривожності в сучасній психологічній науці і практиці та психологічні особливості прояву тривожності у студентів. Емпірично вивчено особливості проявів тривожності у студентської молоді. Проведено інтерпретацію результатів емпіричного вивчення особливості проявів тривожності у студентської молоді. Розроблено психокорекційну програму подолання тривожності у студентів. Надано практичні рекомендації щодо подолання тривожності студентами-психологами.

The features of the main approaches to the phenomenon of anxiety in modern psychological science and practice and the psychological features of the manifestation of anxiety in students have been studied. Empirically studied the peculiarities of the manifestations of anxiety among student youth. An interpretation of the results of an empirical study of the peculiarities of the manifestations of anxiety among student youth was carried out. A psychocorrective program for overcoming anxiety among students has been developed. Practical recommendations for overcoming anxiety by psychology students are given.
Personal readiness for the professional activity of a psychologist
Keywords: особистісна готовність; професійна діяльність; професійна діяльність психолога; значущі характеристики особистісної готовності майбутніх психологів до професійної діяльності; рекомендації; personal readiness; professional activity; professional activity of a psychologist; significant characteristics of personal readiness of future psychologists for professional activity; recommendations